Hebesuncus mollispinus (Eutardigrada, Hypsibiidae), a new species from maritime Antarctica - Pilato, Giovanni; Mcinnes, Sandra J.; Lisi, Oscar (Zootaxa, 2012)
A new species of eutardigrade, Hebesuncus mollispinus sp. nov. is described from Charcot Island, maritime Antarctica.The three known species of Hebesuncus are either widespread with questionable reports from the Antarctic (H.conjungens) or endemic to maritime and continental Antarctica (H. ryani and H. schusteri). Hebesuncus mollispinus sp.nov. differs from its congeners in terms of egg morphology and is further differentiated from H. ryani via a longer buccopharyngeal tube, claw shape and length; and from H. schusteri via a narrower bucco-pharyngeal tube and shorter claws.